Lung Ultrasound Pattern in Healthy Infants During the First 6 Months of Life. (29th May 2020) - Buonsenso, Danilo; Soldati, Gino; Curatola, Antonietta; Morello, Rosa; De Rose, Cristina; Vacca, Maria Eugenia; Lazzareschi, Ilaria; Musolino, Anna Maria; Valentini, Piero
Abstract : Objectives: Lung ultrasound (LUS) has gained a primary role in the diagnosis and management of pleuropulmonary disorders in pediatric practice. However, normal and pathologic patterns are translated from adult studies and have never been specifically studied in children, particularly in infants. This was a prospective observational pilot study aiming to define the normal LUS pattern in healthy infants during the first 6 months of life. Methods: We recruited healthy neonates at 7 to 10 days of life, and these were followed until the sixth month of life (times: 7–10 days, 1 month, 3 months, and 6 months). We excluded neonates with a gestational age before 33 weeks and neonates with cardiac or lung abnormalities or diseases, immune deficiencies, metabolic or genetic conditions, and acute or chronic respiratory diseases. A LUS evaluation was performed by a single certified pediatrician. The chest wall was examined in 18 areas, addressing A‐lines, short and long B‐lines, pleural abnormalities, and subpleural consolidations. Results: Thirty‐seven neonates were enrolled and followed until the sixth month of life, 27 (73%) of whom were born at term (≥37 weeks) and 10 (27%) of whom were born preterm (33–36 weeks). Most of the patients at 7 to 10 days showed multiple B‐lines (long and short) with a progressive normalization toward a normal A pattern at 6 months ( P  < .00001; 95% confidence interval, 13.75–23.24). No infants showed subpleural consolidations or pleural abnormalities. Conclusions: This study has implications for the interpretation of LUS during the first 6 months of life. Most healthy infants show a diffuse pattern of vertical artifacts (B‐lines), and the LUS pattern tends to be similar to the physiologic pattern (A‐lines) after the sixth month of life. The only pathologic LUS findings were pleural irregularities and effusion and subpleural consolidations, which have never been described in healthy infants.